2019
DOI: 10.1109/access.2019.2927016
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying a Paper’s Academic Impact by Distinguishing the Unequal Intensities and Contributions of Citations

Abstract: Citation count is a widely-used indicator for calculating the academic impact of scientific papers, but it is limited because it assumes all citations are of similar value and weights each equally. By examining the influence changes in papers' citation distribution and the cited papers' unequal contributions to the citing ones, this study aims to distinguish citations and, on this basis, evaluate the academic impact of the papers. Three indices of time-weighted citation count, citation width and citation depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Every article should be seen as a carrier of knowledge, and every citation activity between articles contains the diffusion process of knowledge from the cited article to the citing one. In the earlier work done by the authors to detect the typical features influencing the citation impact of an article, we found that a wider citation distribution in various subjects, journals, countries, and institutions had a greater influence on increasing the citation impact of articles [41, 4445]. Thus, this work constructed the feature space F from the aforementioned four features to describe the knowledge diffusion process among articles: …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Every article should be seen as a carrier of knowledge, and every citation activity between articles contains the diffusion process of knowledge from the cited article to the citing one. In the earlier work done by the authors to detect the typical features influencing the citation impact of an article, we found that a wider citation distribution in various subjects, journals, countries, and institutions had a greater influence on increasing the citation impact of articles [41, 4445]. Thus, this work constructed the feature space F from the aforementioned four features to describe the knowledge diffusion process among articles: …”
Section: Methodsmentioning
confidence: 99%
“…While the aforementioned researches seem to suggest that citations may exhibit different levels of importance, they do not explicitly reveal what these levels are and how to detect and use these different levels to evaluate the impact of an article. In one of our previous work, we made a preliminary discussion on the detection of various hidden patterns in citations [41]. The indices of citation intensity, citation width, and citation depth were proposed to distinguish unequal intensities and contributions in citations [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, we calculated the effect size for t-test, effect-size (RS) = 0.2674, effect-size (CS) = 0.3514. (5) We calculated the test statistic T RS , T CS .…”
Section: Results and Analysismentioning
confidence: 99%
“…One possible solution is to construct a multi-dimensional metric in which the importance of citation, social relationships of authors, the relationship between the impact of early citers and scholarly paper impact, and citation inflation need to be explored. [37] prestige of a paper, prestige of author, time yes yes no yes using the citation network, the authorship network and the publication time of the article for predicting future citations [38] the time-weighted citation count, the citation width, the citation depth yes no no yes using entropy weight the three indices statistical feature, network feature, explicit feature, implicit feature, and evaluating paper impact. The number of citations has been used as a metric to evaluate paper impact for a long time [31].…”
Section: Evaluation Of Paper Impactmentioning
confidence: 99%